Probiotic effect in vivo of Roseobacter strain 27-4 against Vibrio (Listonella) anguillarum infections in turbot (Scophthalmus maximus L.) larvae - Planas, Miguel; Pérez-Lorenzo, María; Hjelm, Mette; Gram, Lone; Fiksdal, Ingrid Uglenes; Bergh, Øivind; Pintado, José (Aquaculture, 2006)
11 páginas, 4 figuras, 4 tablas The purpose of this study was to evaluate the probiotic effect of the marine bacterium Roseobacter strain 27-4 in turbot larvae infected with the pathogen Vibrio (Listonella) anguillarum. Initial trials demonstrated that cells of Roseobacter were not harmful to larvae whereas, large amounts of bacterial culture supernatant caused rapid mortality (70% at day 10 compared to 20% in the control). A similar high mortality was, however, also seen, when sterile marine broth was added to the larvae. Presumably both types of medium enhanced growth of opportunistic pathogens. In subsequent trials, both a pathogen, Vibrio anguillarum, and the probiont, Roseobacter strain 27-4, were delivered to the larvae bioencapsulated in rotifers. Accumulated mortality of Vibrio infected larvae increased to 80-90% over 10 days, whereas, mortality in non-infected controls was significantly lower (60-70%). Feeding larvae with rotifers enriched with Roseobacter 27-4 parallel to V. anguillarum infection, brought the accumulated mortality to the level of control indicating a clear in vivo effect. Roseobacter 27-4 could be detected in larvae both by agar plating and by immunohistochemistry, being located in the gastrointestinal lumen, and apparently did not colonise the larval gut and intestinal epithelium. Plate counts decreased when enriched feed was no longer added, suggesting that the probiont, Roseobacter 27-4, should be supplied repeatedly to exert its positive effect. This work was funded by the European Commission (Project PROBE, contract no. Q5RS-2000-31457). Peer reviewed